State of the art of the machine strength rating of lumber (Review) - Fernández-Golfín Seco, J. I.; Díez Barra, M. R.; Hermoso Prieto, E. (Forest Systems, 2001)
Over the last forty years, the machine strength grading of lumber has been developed considerably all over the world, especially in the Nordic and Anglo-Saxon countries. In this paper the beginnings and development of the machine strength grading system are studied. A comparison is also made of the running principles of the machines operating in the market. The variables of the system and their influence in the grading process are also studied. An analysis is also made regarding the mathematical models used to relate classifier variables with predictive variables, measured by the machines, assessing the factors that affect the method and the best way to be taken these into account. Indications about the best way to derive machine settings, according to the standardized methodology approved by the European Committee of Standardization (CEN), are also included. Conclusions are drawn concerning the applicability, present state of the technology, accuracy, reliability and efficiency of the technology, as well as the research necessary to set this technology under way to grade new timber species and the best way to consider all the influencing factors in the grading process.